Context and context meet! A dialogue between the Sitz-im-Leben of Psalm 23 and the South African setting - Mtshiselwa, Ndikho (Old Testament Essays, 2015)
No doubt, Psalm 23 has stimulated a variety of scholarly conversations in OT studies. However, the bearing that this text has on the interpretation of the HB in South Africa is a rarely researched area in scholarship. First, in this article the author considers the probable dating of Ps 23 in order to determine the question of the authorship and intended audience of the text in question. Second, the author attempts to reconstruct the situation of the addressees of Ps 23, and argues that the situation of the psalmist mirrors that of the addressees of the psalm, both in the late exilic and postexilic period. Third, this article draws striking parallels between the context(s) from which the text of Ps 23 emerged and the context of the modern reader of the HB in South Africa. It investigates how a dialogue between the context(s) of the production of Ps 23 and that of the modern reader of the Bible may be established, and more importantly, it submits that the Sitz-im-Leben of the psalm in question could also have positive implications for South Africa.
free